Metod för riskbedömning avseende hand- och armvibrationer - Vid Scania CV AB - Olsson, Malin (2014)
This project, Method for risk assessment of hand-arm vibrations, is a degree project in industrial design at Luleå University of Technology. The project was conducted at Scania CV AB in Södertälje during spring semester 2014. The aim with the project was to create a method for risk assessment of hand-arm vibrations adapted for Scania’s production system. The goal was a method that will ensure Scania to control the exposure of vibrations. Literature and interviews were performed to gain knowledge about vibrations and what factors that affect exposure of vibrations. Measurements were made in different areas to complement the literature. The result is a method for risk assessment of hand-arm vibrations and also a method to calculate the allowed time of use until the limits of vibrations are reached. The result have been verified with measurements and the method is reasonable and reliable. It suits for production systems with repeating tasks and when the exposure time is easy to measure. It is recommended that;  Scania complement the risk assessment with a guideline and then implement it in Scania’s work routine.  The method is performed by a safety engineer or by a person with similar competence.  Scania develop a course about vibrations for the employed. Validerat; 20140626 (global_studentproject_submitter)